Anak Berkebutuhan Khusus Tunanetra - Muhammad Rayhan Lubis; Maulida Zahara; Apria Cahyani; Amira Qhistina; Aura Sisca Maria Sinaga; Eli Aulia; Trisna Ningsih; Novita Friska (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2025)
Visual impairment is a general term used to describe partial or complete loss of vision function. This research uses a qualitative approach. Observation results show that by implementing appropriate teaching methods, blind children can learn effectively. Good interaction between teachers and students, as well as the use of braille and audio visual aids, greatly contribute to a positive learning process.